PENYULUHAN PEMBUATAN SABUN COLEK SECARA MANDIRIPADA IBU RUMAH TANGGA DI DUSUN TANGGUL, DESA BOTO, WONOSARI, KLATEN, JAWA TENGAH - Indah Susantun (UII, 2014)
Needs of cleaning tools such as soap is getting increase in line with the increase ofenvironmental pollution annually that come from household waste and loundry.The useof less environmentally soap that can polluting the environment is getting worse.Therefore, the manufacture of soap program is a program aimed at training to the PKK(Dasawisma) member. This program is carried out so that the mother-housewife canmake their own cream soap so as to save on household expenses. In addition, by makingthis soap theirself, the housewife can be moreaware of any matter contained in a dab ofsoap so as to avoid skin irritation or pollution on the environment.